THE EFFECT OF DESTINATION BRAND EXPERIENCE ON BEHAVIORAL INTENTION THROUGH TOURIST SATISFACTION AS A MEDIATON: (ASSOCIATIVE STUDY OF THE “JOGJA ISTIMEWA” BRAND) - Intan Nurhayati; Herlan Suherlan; Tatan Suhendar (International Journal of Sustainable Competitiveness on Tourism, 2022)
Brand can be a tool to provide differentiation and competitive advantage for tourism destinations. It is important to see how the brand performs in providing a positive image of the destination. Brand performance is seen through the influence of destination brand experience on tourist behavior intentions. The concept of destination brand experience can be seen through the sensory, affective, intellectual, and behavioral dimensions. So this study aims to see the effect of destination brand experience on tourist behavioral intention through tourist satisfaction. This research was conducted with an associative method with a descriptive quantitative approach. The number of samples used was 304 domestic tourist respondents. The results of this study indicate that the destination brand experience has been carried out well, but optimization is still needed. Tourist satisfaction with the destination brand experience is at a Satisfied level, tourists also say they will do positive word of mouth and make return visits. Then the variables between destination brand experience and behavioral intention influence one another through tourist satisfaction as a mediation.